Chayote and cucumber peels as raw material for edible leathers (pestils): valorization of vegetable residues - de Menezes Rodrigues, Giovana; dos Santos Garcia, Vitor Augusto [UNESP]; Vanin, Fernanda Maria; Yoshida, Cristiana Maria Pedroso; de Carvalho, Rosemary Aparecida (Elsevier, 2025)
Edible leathers (pestils) are dehydrated products obtained from drying vegetable purees, resulting in flexible sheets with a leather-like texture. They represent a practical, nutritious and stable healthy snack option. The objective of the study was to evaluate the properties and stability of leathers (pestils) based on purees. Formulations were prepared with varying concentrations of chayote peel puree (60, 70 and 80 g/100 g) and cucumber (40, 50 and 60 g/100 g), with agar-agar (2 g/100 g). The leathers were produced using the tape-casting technique and dried at 50 °C for 9h. Characterization included microstructural and mechanical properties, and storage stability under accelerated conditions for 40 days. Samples with higher concentrations of chayote peel puree exhibited greater thickness (0,199–0,229 mm), puncture force (13,34-14,33 N), and puncture deformation (1,41-1,47 %) compared to those formulated with cucumber peel puree. Water content increased up to fourfold during storage, promoting the realease of bioactive compounds and antioxidant activity. Cucumber peel leathers showed better color stability and a lower browning index, likely due to natural antioxidants. Higher puree concentrations also led to increased total phenolic content and antioxidant activity. These results highlight the potential of vegetable peels in developing sustainable, nutritious snacks with good storage stability.